Special Needs at Different Educational Levels: A Forecast of 2020 - Karagiannidis, Charalampos; Kouroupetroglou, Christos; Koumpis, Adamantios (International Journal of Emerging Technologies in Learning (iJET), 2012)
This paper reports on the results of the eAccessibility 2020 study which was funded by the European Commission to explore and analyse the relationships between the emerging ICT landscape in the societal and economic context, and the development and provision of assistive technologies and eAccessibility within a perspective of the next 10 years. The methodology of the study included both desk research and direct contact with relevant actors through 2011 and 2012. The results of the study are summarised for different educational levels (from primary-school to post-university) and are presented in terms of core issues, which are the most important developments in the area that will concentrate research and development efforts; roadmaps, which are most probable elements of a future research agenda in the area; and potential scenarios, which are indicative and not necessarily representative examples of use cases that may appear in the field.